(3GdfGSN hGdefShNs - (3ceGd GdOjf, GHf GdYJGFbj, GHf GdYJGFbj, YHO GdQMef Hf eMeO Hf EHQGgje, J fMh (B790(3g` (B1388(3es ((3eMeO WGgQ GdSeGhjs)
(3ChdgG (B:s
(3ChdgG(B: (3GdMeO ddg ecGaCI dCaVGdI (B... (3agPg QSGdI aj Yde GdfGSN hGdefShN, aEf Pdc Chdi eG jLH Cf jHOC Hg ef Ydhe GdbQBfs
(3BNQgG (B:s
(3BNQgG(B: (3ShQI GdfUQ Edi BNQ GdbQBf djS ajgG fGSN hdG efShN, agPG eG CQOfG PcQgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B3: 330s
(3GdPQjYI, L(B24: 9s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs